Difficulties in HAM/TSP diagnosis - Carla Maria Sena Andrade Slater; Luiz Claudio Pereira Ribeiro; Marzia Puccioni-Sohler (Arquivos de Neuro-Psiquiatria)
The World Health Organization recommends the use of Osame's criterion (1990) for the diagnosis of HTLV-I-associated myelopathy (HAM/TSP). In 2006, a group of neurologists developed a Brazilian criterion that can diagnose HAM/TSP from its onset. OBJECTIVE: It was to test the agreement between both criteria. METHODS: The study included evaluation of clinical and laboratory findings of 35 patients. The ELISA, Western blot and/or polymerase chain reaction was used to search for anti-HTLV-I antibodies. The analysis of agreement was based on the calculation of Kappa. RESULTS: Concordance of 100% (Kappa=1) occurred in cases of "defined" HAM/TSP, but not in patients with "probable" diagnosis. CONCLUSION: The Brazilian criteria was as effective as Osame's criteria for the diagnosis of "defined" HAM/TSP. However, both require more specific biological markers in cerebrospinal fluid for the laboratory diagnosis of probable cases.